2020
DOI: 10.1101/2020.03.12.988402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid changes in brain activity during learning of grapheme-phoneme associations in adults

Abstract: Learning to associate written letters with speech sounds is crucial for the initial phase of acquiring reading skills. However, little is known about the cortical reorganization for supporting letter-speech sound learning, particularly the brain dynamics during the learning of grapheme-phoneme associations.In the present study, we trained 30 Finnish participants (mean age: 24.33 years, SD: 3.50 years) to associate novel foreign letters with familiar Finnish speech sounds on two consecutive days (first day ~ 50… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 107 publications
1
4
0
Order By: Relevance
“…Specifically, in the audio-visual condition as compared to the unimodal condition, the processing of words led to more significantly stronger activation in the parietal areas. This is in line with a previous MEG study in Finnish school children that emphasizes the crucial role of the parietaltemporal cortex in the early phase of reading [9]. The parietal areas may be involved in early audio-visual integration [12,42,43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, in the audio-visual condition as compared to the unimodal condition, the processing of words led to more significantly stronger activation in the parietal areas. This is in line with a previous MEG study in Finnish school children that emphasizes the crucial role of the parietaltemporal cortex in the early phase of reading [9]. The parietal areas may be involved in early audio-visual integration [12,42,43].…”
Section: Discussionsupporting
confidence: 92%
“…An increasing body of studies has explored the mechanisms underlying audiovisual integration of letters and speech sounds [7][8][9] and consistently demonstrated the superiority of audio-visual integration over processing letters and speech sounds separate [10,11]. For example, a magnetoencephalography (MEG) study showed enhanced brain activity predominantly in the right temporal-occipital-parietal junction and the left and right superior temporal sulci for audio-visual integration of phonemes and graphemes [12].…”
Section: Introductionmentioning
confidence: 99%
“…IPS has previously been implicated in the grapheme-phoneme conversion process (Dehaene-Lambertz et al, 2018;Xu et al, 2020). Given that IPS shows both word frequency and lexicality sensitivity, its role in sub-lexical processing might appear to be questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Language abilities are associated with the perisylvian brain network within the left hemisphere, including inferior frontal areas, the superior temporal cortex and the inferior parietal lobule (Price, 2012). Reduced activation of these brain regions has been related to phonological and visual‐verbal mapping deficits in developmental dyslexia (Blomert, 2011; Démonet, Taylor, & Chaix, 2004; Richlan, 2012, 2019; Xu, Kolozsvari, Oostenveld, & Hämäläinen, 2020). Visuo‐spatial attention has instead been related to posterior brain areas bilaterally, including the temporal parietal junction, the superior parietal lobule (SPL) and the frontal eye fields (Behrmann, Geng, & Shomstein, 2004; Carrasco, 2011).…”
Section: Is Vas Performance a Marker Of Visuo‐attentional Processing?mentioning
confidence: 99%